Pengaruh Intelllectual Capital dan Corporate Social Responsibility terhadap Nilai Perusahaan: Pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2018-2020 - Faulin Adelina; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2021)
This study was to determine the influence of intellectual capital and corporate social responsibility on firm value. This research method is quantitative. The population in this study is the mining sector companies on the Indonesia Stock Exchange from 2018 to 2020. The sample of this study was determined by purposive sampling. Data analysis techniques for hypothesis testing using multiple regression analysis. The results show that intellectual capital has no significant effect as well as corporate social responsibility on firm value. This is due to the low interest of investors in other aspects outside of physical and financial assets. investors are more focused on maximizing profit as a short term goal. it can be suggested that: (1) Companies should increase their assets to increase company size so that companies have more financial funds to manage their IC performance and create more added value, and (2) For future researchers, it is recommended to increase the number of sample companies, adding other variables and using other proxies in further research.